2009
DOI: 10.5014/ajot.63.4.453
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Family Occupations: Family Member Perceptions of a Specialized Environment for Children With Mental Retardation

Abstract: A sense of intimacy and relaxation, provided by the Snoezelen environment, is important in facilitating family occupations for this population. Interventions in occupational therapy must be designed that take these requirements into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…The last question revealed participant ambivalence about multi‐sensory environments and reflected earlier findings of Sachs and Nasser (), who reported multi‐sensory environments could help overstimulated children engage in events by temporarily suspending reality. However, like our participants, they reported some environments can contribute to overexcitement, and while popular, how and why these spaces are effective is still ambiguous.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The last question revealed participant ambivalence about multi‐sensory environments and reflected earlier findings of Sachs and Nasser (), who reported multi‐sensory environments could help overstimulated children engage in events by temporarily suspending reality. However, like our participants, they reported some environments can contribute to overexcitement, and while popular, how and why these spaces are effective is still ambiguous.…”
Section: Discussionsupporting
confidence: 61%
“…Multi-sensory environments are claimed to promote emotional wellness, enhance communication skills, enable relaxation, offer opportunities for cognitive development and increase adaptive behaviours and selfdetermination. Research evidence supporting their use tends to focus on patient populations affected by dementia, psychiatric disturbances or severe and profound multi-disabilities (Chalmers, Harrison, Mollison, Molloy, & Gray, 2012;Sachs & Nasser, 2009). More recently, a trend has emerged to promote using them in community and educational settings (Kaplan et al, 2006;Stephenson & Carter, 2011;West, Melvin, McNamara, & Gordon, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These studies reported on patient perceptions related to OT interventions, the identification of strategies OT’s use to teach caregivers, and observations of real-life implementation of best practices advocated by OT. The two studies reporting patient perceptions (Hemmingsson et al, 2009; Sachs & Nesser, 2009) were classified as reporting on Personal Factors. The two remaining studies (Colyvas, Sawyer & Campbell, 2010; Yonkman, O’Neil, Talty & Bull, 2010) were classified as reporting on Environmental Factors.…”
Section: Resultsmentioning
confidence: 99%
“…Puis, une étude s'est intéressée aux familles d'enfants présentant une déficience intellectuelle sévère et profonde vivant des expériences singulières dans ce lieu (Sachs & Nasser, 2009). Les chercheurs ont analysé la manière dont Snoezelen facilitait le rôle des parents et de la fratrie.…”
Section: Snoezelen Auprès D'enfants Adolescents Et Adultes Présentanunclassified